Sentinel approach to detect emerging causes of work-related respiratory diseases. (21st December 2019) - Zhou, A Y; Seed, M; Carder, M; Money, A; Van Tongeren, M; Agius, R
Abstract: Background: The world of work is continually changing, and this could result in new and emerging risks being introduced, including those that may cause work-related respiratory diseases (WRRD). Aims: To describe recently emerging and new cases of WRRD and the relevant methodology using data in a national occupational respiratory disease surveillance scheme in the UK. Methods: Incident cases of respiratory diseases reported by physicians to the Surveillance of Work-related and Occupational Respiratory Disease (SWORD) between January 2015 and December 2017 were included. Potentially emerging respiratory hazards manifesting in SWORD data were identified with the following hierarchical approach: (i) new respiratory disease not previously associated with work, (ii) specific exposure/agent not previously associated with WRRD and (iii) industry and/or occupation not previously associated with WRRD. Results: A total of 1215 cases of WRRD were reported to SWORD between January 2015 and December 2017. No new WRRD were identified. Thirteen potentially emerging causes of occupational asthma were identified, including exposures to agents such as ninhydrin. Four potential new causes were identified for interstitial pneumonia, which included wood and brass dust. Two potentially emerging causes of WRRD were identified for inhalational accidents (green coffee and nitrocellulose), hypersensitivity pneumonitis (diphenylmethane diisocyanate and salami mould), rhinitis (morphine and Amaranthus quitensis) and sarcoidosis (prions and horses). Conclusions: Continuous monitoring and reporting of any new work-related disease is a critical function of any occupational disease reporting scheme. Potential emerging causes of work-related health risks have been identified by using a simple and systematic way of detecting emerging causes of WRRDs.